The Cotton Apoplastic Protein CRR1 Stabilizes Chitinase 28 to Facilitate Defense against the Fungal Pathogen Verticillium dahliae. Issue 2 (16th January 2019) - Han, Li-Bo; Li, Yuan-Bao; Wang, Fu-Xin; Wang, Wen-Yan; Liu, Jun; Wu, Jia-He; Zhong, Nai-Qin; Wu, Shen-Jie; Jiao, Gai-Li; Wang, Hai-Yun; Xia, Gui-Xian
Abstract : Cotton Cys-rich repeat protein 1 participates in defense responses by protecting chitinase 28 from cleavage by a Ser protease of Verticillium dahliae. Abstract: The apoplast serves as the first battlefield between the plant hosts and invading microbes; therefore, work on plant-pathogen interactions has increasingly focused on apoplastic immunity. In this study, we identified three proteins in the apoplast of cotton ( Gossypium sp) root cells during interaction of the plant with the fungal pathogen Verticillium dahliae . Among these proteins, cotton host cells secrete chitinase 28 (Chi28) and the Cys-rich repeat protein 1 (CRR1), while the pathogen releases the protease VdSSEP1. Biochemical analysis demonstrated that VdSSEP1 hydrolyzed Chi28, but CRR1 protected Chi28 from cleavage by Verticillium dahliae secretory Ser protease 1 (VdSSEP1). In accordance with the in vitro results, CRR1 interacted with Chi28 in yeast and plant cells and attenuated the observed decrease in Chi28 level that occurred in the apoplast of plant cells upon pathogen attack. Knockdown of CRR1 or Chi28 in cotton plants resulted in higher susceptibility to V. dahliae infection, and overexpression of CRR1 increased plant resistance to V . dahliae, the fungus Botrytis cinerea, and the oomycete Phytophthora parasitica var nicotianae . By contrast, knockout of VdSSEP1 in V. dahliae destroyed the pathogenicity of this fungus. Together, our results provide compelling evidence for a multilayered interplay of factors in cotton apoplastic immunity.